2007
DOI: 10.1130/g23103a.1
|View full text |Cite
|
Sign up to set email alerts
|

Fish tooth δ18O revising Late Cretaceous meridional upper ocean water temperature gradients

Abstract: The oxygen isotope composition of fossil fish teeth, a paleoupper ocean temperature proxy exceptionally resistant to diagenetic alteration, provides new insight on the evolution of the low-to middlelatitude thermal gradient between the middle Cretaceous climatic optimum and the cooler latest Cretaceous period. The new middle Cretaceous low to middle latitude thermal gradient agrees with that previously inferred from planktonic foraminifera 8 ls O recovered from Deep Sea Drilling Project and Ocean Drilling Prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 29 publications
7
63
1
Order By: Relevance
“…The Maastrichtian records a cooling that settles back the temperature to the mean base level of the Early Cretaceous. Fish teeth δ 18 O data gathered by Puceat et al (2007) have already demonstrated that marine temperatures of the climatic optimum of the middle Cretaceous and of the cooler latest Cretaceous were separated by 7 • C on average. Amplitude of the cooling estimated here is of the same order.…”
Section: Discussionmentioning
confidence: 99%
“…The Maastrichtian records a cooling that settles back the temperature to the mean base level of the Early Cretaceous. Fish teeth δ 18 O data gathered by Puceat et al (2007) have already demonstrated that marine temperatures of the climatic optimum of the middle Cretaceous and of the cooler latest Cretaceous were separated by 7 • C on average. Amplitude of the cooling estimated here is of the same order.…”
Section: Discussionmentioning
confidence: 99%
“…1,000 ppm for these periods. For the Cretaceous, comparisons of our simulations with oceanic latitudinal thermal gradients reconstructed from paleoceanographic data (17)(18)(19)(20)(21)(22)(23)(24)(25) show that pCO 2 of 2,240 ppm is required to produce sea surface temperatures comparable with data for the Aptian and Cenomanian, whereas for the Maastrichian, data-derived sea surface temperature gradient is better reproduced at 1,120 ppm (Fig. S2).…”
mentioning
confidence: 89%
“…The most recent studies (e.g., Puceat et al 2007), in which the oxygen isotope content of fossil fish teeth was used, show that the low-to-mid-latitude SST gradients in the Cretaceous are very similar to the present-day gradients. The results obtained by Amiot et al (2004) are very similar to those reported by Puceat et al (2007), although the reconstructed temperatures in the study conducte by Amiot et al are the mean air temperatures in coastal lowlands.…”
Section: Cretaceous Climatementioning
confidence: 99%